2009
DOI: 10.1213/ane.0b013e3181b5881c
|View full text |Cite
|
Sign up to set email alerts
|

Difficult Mask Ventilation

Abstract: Mask ventilation is the most fundamental skill in airway management. In this review, we summarize the current knowledge about difficult mask ventilation (DMV) situations. Various definitions for DMV have been used in the literature. The lack of a precise standard definition creates a problem for studies on DMV and causes confusion in data communication and comparisons. DMV develops because of multiple factors that are technique related and/or airway related. Frequently, the pathogenesis involves a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(106 citation statements)
references
References 88 publications
0
103
1
2
Order By: Relevance
“…Montague et al described the placement of nasopharyngeal airways and Jaques catheters under direct vision using the GlideScope TM (Verathon Medical United Kingdom Ltd, High Wycombe, UK) in patients having cleft palate repair [1]. Likewise, Gordon et al Used the GlideScope to inspect the airway, with minimal stimulation, following facial reconstructive surgery [2]. Similarly, we have found the Airtraq TM Optical Laryngoscope (Prodol Meditec SA, Vizcaya, Spain) of use following thyroid surgery.…”
Section: Extended Roles For Videolaryngoscopymentioning
confidence: 78%
See 1 more Smart Citation
“…Montague et al described the placement of nasopharyngeal airways and Jaques catheters under direct vision using the GlideScope TM (Verathon Medical United Kingdom Ltd, High Wycombe, UK) in patients having cleft palate repair [1]. Likewise, Gordon et al Used the GlideScope to inspect the airway, with minimal stimulation, following facial reconstructive surgery [2]. Similarly, we have found the Airtraq TM Optical Laryngoscope (Prodol Meditec SA, Vizcaya, Spain) of use following thyroid surgery.…”
Section: Extended Roles For Videolaryngoscopymentioning
confidence: 78%
“…As they point out, the use of a non-Luer connector would not have prevented this error [2]. I would like to commend a simple 10-step systems solution for minimising the chance of this happening in future: Patel suggests that test ventilation may lighten anaesthesia and promote difficulty.…”
mentioning
confidence: 99%
“…Every anesthesiologist should acquire the skills for mask ventilation [1]. DMV is a situation in which it is not possible for the anesthesiologist to provide adequate face mask ventilation due to an inadequate mask seal, excessive gas leakage or excessive resistance to ingress or egress of gas [3].…”
Section: Discussionmentioning
confidence: 99%
“…It includes difficult intubation (DI), difficult mask ventilation (DMV) or both. Since mask ventilation is a basic fundamental skill in airway management, every anesthesiologist should acquire skills for mask ventilation and should be knowledgeable about the causes of DMV and consider alternative options including oropharyngeal airway, nasopharyngeal airway, laryngeal mask airway, transtracheal jet ventilation, cricothyrotomy, and awake fiberoptic intubation (AFOI) when the mask ventilation is difficult [1]. Mask ventilation is the first step of airway management before endotracheal intubation or insertion of any airway devices.…”
Section: Introductionmentioning
confidence: 99%
“…Independent predictors for difficult face mask ventilation are: obesity, aged 55 years and above, history of snoring, lack of teeth, the presence of a beard, Mallampati Class III or IV, and abnormal mandibular protrusion test. (18) Predictors for difficult intubation include: decreased interdental and thyromental distances, increased Mallampati scores, and decreased neck movement. (19,20) One study demonstrated 12 independent predictors of combined difficult face mask ventilation and laryngoscopy: aged 46 years and above; body mass index ≥ 30; male gender; Mallampati Class III or IV; neck mass or radiation changes; limited thyromental distance; sleep apnoea; limited cervical spine mobility; limited jaw protrusion; thick neck; presence of teeth; and beard.…”
Section: Causes Location and Degree Of Obstructionmentioning
confidence: 99%